2020
DOI: 10.1038/s41598-020-75320-1
|View full text |Cite
|
Sign up to set email alerts
|

Urinary podocyte mRNAs precede microalbuminuria as a progression risk marker in human type 2 diabetic nephropathy

Abstract: Earlier detection of progression risk in diabetic nephropathy will allow earlier intervention to reduce progression. The hypothesis that urinary pellet podocyte mRNA is a more sensitive progression risk marker than microalbuminuria was tested. A cross sectional cohort of 165 type 2 diabetics and 41 age and sex-matched controls were enrolled. Podocyte stress (Urinary pellet podocin:nephrin mRNA ratio), podocyte detachment (Urinary pellet podocin mRNA:creatinine ratio: UPPod:CR) and a tubular marker (Urinary pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 51 publications
(84 reference statements)
1
32
0
Order By: Relevance
“…T2DM causes the aggregation and release of inflammatory factors that damage the kidneys and lead to TN formation. In this process, MAU is an early predictor of diabetic nephropathy, which reflects the balance between glomerular filtration and renal tubular reabsorption of albumin [28,29]. erefore, we infer that the underlying mechanism of positive correlation between MAU and TNs might be attributed to inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…T2DM causes the aggregation and release of inflammatory factors that damage the kidneys and lead to TN formation. In this process, MAU is an early predictor of diabetic nephropathy, which reflects the balance between glomerular filtration and renal tubular reabsorption of albumin [28,29]. erefore, we infer that the underlying mechanism of positive correlation between MAU and TNs might be attributed to inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have confirmed that the detection of podocyte mRNA excretion is a more sensitive marker than proteinuria and creatinine. A significant increase in podocyte mRNA loss can be detected in kidney diseases negative for albuminuria or proteinuria 17,42,43 . However, in this study, at age of 3 weeks, a higher level of proteinuria in premature rats was detected, while the change in the podocyte mRNA excretion level was mild, even though there was no significant difference between preterm and full-term 24-h podocyte mRNA excretion.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was removed, the pellet suspended in 1.5 mL of diethyl pyrocarbonate-treated phosphate-buffered saline, and centrifuged at 12000 × g for 5 min at 4°C. The washed pellet was resuspended in RLT/β-mercaptoethanol buffer (RNeasy Kit; Qiagen, Germantown, MD) and frozen at −80°C until RNA extraction (16,23,28). cDNA standard curves were constructed using these serially diluted standards as described previously (16,23,28).…”
Section: Extraction Of Rna From Human Urinary Sedimentmentioning
confidence: 99%
“…The washed pellet was resuspended in RLT/β-mercaptoethanol buffer (RNeasy Kit; Qiagen, Germantown, MD) and frozen at −80°C until RNA extraction (16,23,28). cDNA standard curves were constructed using these serially diluted standards as described previously (16,23,28). The concentration of urinary sediment podocin mRNA was standardized by the creatinine concentration and was expressed as M/g creatinine.…”
Section: Extraction Of Rna From Human Urinary Sedimentmentioning
confidence: 99%